Ökonomie und Zukunft - Cattini, Marco (bu,press, 2015)
What does modern economics mean when it talks about the future and predicts the future? Where does it reach out to when it wants to secure the future for people or keep it open? How was the future experienced and thought of in Greek times, an epoch in which the possibility of theory formation first arose, and thus the foundation was laid for a knowledge of the future? This volume brings together the contributions to two colloquia held at the Free University of Bozen-Bolzano in 2013 and 2014 on the relationship between economics and the future and aims to point out the questionable nature of this relationship. With this intention, the terms "economy" and "future" lose their unambiguity and become questionable in their turn.; Was meint die moderne Wirtschaftswissenschaft, wenn sie von Zukunft redet und Künftiges vorhersagt? Wohin greift sie aus, wenn sie die Zukunft für den Menschen sichern oder offen halten will? Wie wurde Zukunft im Griechentum erfahren und gedacht, einer Epoche, in der zuerst die Möglichkeit einer Theoriebildung aufkam, und damit der Grundstein gelegt wurde für ein Wissen von Zukunft? Der vorliegende Band versammelt die Beiträge zu zwei in den Jahren 2013 und 2014 an der Freien Universität Bozen abgehaltenen Kolloquien zum Verhältnis von Ökonomie und Zukunft und möchte auf das Fragwürdige dieses Verhältnisses hinweisen. In dieser Absicht verlieren die Begriffe "Ökonomie" und "Zukunft" ihre Eindeutigkeit und werden ihrerseits fragwürdig.